Inspiring Children's Mathematical Activity Through Contact with a Picture Book - BARBARA BILEWICZ-KUŹNIA (Edukacja Elementarna w Teorii i Praktyce, 2021)
Children’s literature has a cognitive value and is a source of aesthetic experiences. Picture books with mathematical content are a special type of children’s books. The study aims to show that picture books where mathematical text is combined with images in an aesthetic form provide impulses to create educational situations that inspire mathematical activity. Based on the classification of mathematical activity by Ewa Kozak-Czyżewska, we developed our methodological proposals for stimulating creative and imitative mathematical activity in children. These suggestions are presented on the basis of our work with two books: Numbers written by Jacek Cygan and At our house written by Isabel Minhós Martins and Madalena Matoso. For the purpose of this study, educational classes with the use of mathematical literary texts were conducted for six-year-old children in kindergarten. It has been shown that picture books can inspire creative and imitative mathematical activity in children. By providing positive experiences, these texts can support the processes of learning mathematics, awaken children’s motivation to calculate and use mathematics in everyday life. The presented study may be used as a model of working with picture books with mathematical content in kindergarten.